FORMULATION OF ECONAZOLE NITRATE AS A TOPICAL SOLUTION - LAITH HAMZA SAMIN (College of Pharmacy University of Baghdad, 2017)
Econazole nitrate (EN) is considered as the most effective agent for the treatment of all forms of dermatomycosis caused by dermatophytes. This study was carried out to formulate a stable Econazole nitrate solution for a topical use through preparation of different formulas and selected the most suitable one. The results indicated that the use of propylene glycol and ethanol as a vehicle for EN which is very slightly soluble in water gave amore stable formula as EN topical solution, with a shelf life of about 3.15 years .The data also indicated that the light accelerated the degradation of EN, while the type of container (glass or plastic) had no effect on the rate of drug. The overall results of this study suggest that the selected formula could be used as a topical solution for EN.